Determination of the Energy Efficient Speed of the Working Body of the Agitator for Small Biogas Reactors - Spodoba M.O.; Spodoba О.O.; Kovalchuk S.I.; Oliinik Yu.O. (Problems of the Regional Energetics)
The aim of the work is to determine the energy-efficient speed level of a two-tier paddle mixer with blades installed at an angle of 90° to improve the energy efficiency of the biogas formation process in small biogas reactors. To achieve the set goals, physical methods, three-dimensional model- ing, processing and visualization of results in application programs were used. The working hypothe- sis of the research is that 3D modeling will allow determining the nature of the distribution of biomass flows and the amount of energy expended depending on the rotation speed of the mixing device. The most important result of the study is the obtaining of graphical dependencies of the trajectories of movement of elementary volumes and the velocities of substrate flows at different rotation speeds of the stirrer. The significance of the research results is that, based on the flows of raw materials in the reactor, it was established that for a reactor with the geometric parameters specified in the work, the energy-efficient rotation frequency of the paddle mixer with blades at an angle of 90° is within 40…50 rpm. The average speed of the substance is in the range of 0.273 – 0.348 m/s. It was found that the dependence of the consumed energy on the mixer rotation speed corresponds to a power function. The percentage of useful energy spent in starting and operating modes for different rotation speeds was determined. The obtained data can be used for upgrading and designing mixing systems in small bio- gas reactors.